Quality of Coffea arabica seedlings produced in different nurseries in southern Minas Gerais, Brazil - dos Passos, Anderson Barreto; de Melo, Bruno Manoel Rezende; Ferreira, Sindynara; Castro, Douglas Goulart; dos Santos, Telma Miranda; Guedes, Leonardo Alves (Revista Agrogeoambiental, 2021)
Obtaining high-quality seedlings is a step of fundamental importance for the successful implementation of a coffee crop, which can be measured by evaluating seedling morphological and quality parameters. This study examines the quality of coffee seedlings produced in nurseries in the municipalities of Inconfidentes, Ouro Fino, and Jacutinga, southern Minas Gerais State, Brazil. The experiment was carried out in nurseries here termed 1, 2, 3, 4, 5, 6, 7 and 8, from 05/28/2017 to 02/28/2018. The experiment was developed in an 8 × 2 factorial arrangement consisting of 8 seedling nurseries and 2 cultivars (Catuaí strains IAC 62 and 144) evaluated in 3 replicates containing 8 seedlings each. The following traits were evaluated: leaf area (LA), total dry matter (TDM), shoot: root ratio (S: R), plant height: stem diameter ratio (HDR), and Dickson quality index (DQI). Data were subjected to combined analysis and, after significant differences were detected (p<0.05), the Scott-Knott test of means was applied. The management adopted in the nurseries influenced the development of the evaluated cultivars. Seedlings from nursery 5, of both evaluated cultivars; and from nursery 8, of cultivar IAC 144, exhibited a DQI above 0.2, indicating superior quality. Only nursery 5 showed seedlings of adequate quality for both cultivars. Regardless of their location, the other coffee-seedling nurseries still did not produce seedlings of satisfactory quality to be taken to the field.